The war against poetry - Fraser, Russell A. (Princeton legacy library., 1970)
The attack on poetry and the theater which occurred in England during the 16th and 17th centuries has been the subject of numerous scholarly investigations. This "war against poetry" was, in Professor Fraser's view, part of a larger cultural movement: the disengagement of the modern world from its medieval antecedents.Originally published in 1971.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.